USING AI TECHNOLOGY TO SUPPORT LEARNING AND BOOST STUDENT INDEPENDENCE AT SMA MUHAMMADIYAH PK SURAKARTA - Muhammad Aliq Aulia; Kresno Ario Tri Wibowo; Irfan Nugraha; Deshinta Arrova Dewi (Ikatan Dosen Menulis, 2026)
Background: The rapid development of Artificial Intelligence (AI) technology has significantly influenced the education sector, particularly at the senior high school level. However, preliminary observations at SMK Muhammadiyah PK Surakarta indicated that students’ understanding of AI was still limited prior to the implementation of this community service activity. Initial assessments showed that only about 20% of students had basic knowledge of AI concepts, including its functions, limitations, and ethical use in learning contexts. This gap between technology exposure and conceptual understanding highlights the importance of structured AI socialization to support learning and foster student independence. Objective: This community service activity aims to support learning processes and boost student independence by strengthening AI literacy through systematic socialization and educational activities. Method: The program was implemented through AI socialization sessions, interactive presentations, demonstrations of AI-based learning tools, and guided discussions. The activity was carried out through an international collaboration with INTI International University, with academic partnership support from Prof. Dr. Deshinta Arrova Dewi. The evaluation employed a one-group pre-test and post-test design to measure changes in students’ understanding of AI. Result: The post-test results indicated a substantial improvement in students’ understanding of Artificial Intelligence. The level of comprehension increased from approximately 20% before the socialization to 89% after the activity, reflecting an overall improvement of 69%. This improvement demonstrates that AI socialization effectively enhances students’ digital literacy, learning engagement, and capacity for independent learning. Conclusion: These findings indicate that AI socialization is essential and effective for senior high school students. The community service activity focusing on Using AI Technology to Support Learning and Boost Student Independence can be well accepted by the target participants and has strong potential to be implemented sustainably as an innovative learning support model in secondary education.